ChemInform Abstract: Fate of a Giant Mo72Fe30‐Type Polyoxometalate Cluster in an Aqueous Solution at Higher Temperature: Understanding Related Keplerate Chemistry, from Molecule to Material. Issue 44 (14th October 2013) - Mekala, Raju; Supriya, Sabbani; Das, Samar K.
Abstract Reflux of an aqueous solution of [Mo72Fe30O252 (OAc)12{Mo2O7(H2O)}2 {H2Mo2O8(H2O)}(H2O)] ·150H2O for 36 h results in the formation of nanoparticles of Fe2(MoO4)3 in the form of a yellow precipitate.